Scalable fabrication of tunable titanium nanotubes via sonoelectrochemical process for biomedical applications - Mansoorianfar, Mojtaba; Khataee, Alireza; Riahi, Zohreh; Shahin, Khashayar; Asadnia, Mohsen; Razmjou, Amir; Hojjati-Najafabadi, Akbar (Elsevier, 2020)
Titanium does not react well with the human tissues and due to its bio-inert nature the surface modification has yet to be well-studied. In this study, the sonoelectrochemical process has been carried out to generate TiO2 nanotube arrays on implantable Ti 6-4. All the prepared nanotubes fill with the vancomycin by immersion and electrophoresis method. Drug-releasing properties, antibacterial behavior, protein adsorption and cell attachment of drug-modified nanotubes are examined by UV-vis, flow cytometry, modified disc diffusion, BSA adsorption, and FESEM, respectively. The most uniform morphology, appropriate drug release, cell viability behavior and antibacterial properties can be achieved by samples anodized in the range of 60-75 V. Also improves the adsorption of BSA protein in bone healing and promotes osteoblast activity and osseointegration. Drug loading efficiency increases up to 60% via electrophoresis comparing the immersion method for anodized sample in 75 V. While electrophoresis does not affect the amount of vancomycin adsorption for lower voltages. Besides, the present study indicates that an anodized sample without drug loading has no antibacterial activity. Moreover, 28-days drug releasing from nanotubes is investigated by mathematical formula according to Fickian's law to find an effective dose of loaded drug.
Keywords: TiO2 nanotube; Flow cytometry; S. aureus; Drug-modified nanotube; Antibacterial properties